Analysis of the Influence of Islamic Social Reporting Disclosure on the Growth of Islamic Banks (Study of Sharia Commercial Bank 2017-2021 Period) - Raihan Ramadhanty; Saparuddin Siregar; Juliana Nasution (Jurma : Jurnal Program Mahasiswa Kreatif, 2022)
This study aims to empirically examine the effect of Islamic Social Reporting on the Growth of Islamic Banking, namely Islamic Commercial Banks for the 2017-2021 period. This study uses a quantitative approach. The type of variable data is secondary data, namely data obtained from the annual financial report published on the official website of each bank for the period 2017-2021. The analytical method used is the panel data regression method. The data analysis techniques used in this study include Descriptive Statistical Analysis, Model Selection (FEM, CEM REM, Chow Test, Hausman Test, and Lagrange Multiplier Test). Classical Assumption Test consists of the Normality Test, Multicollinearity Test, Autocorrelation Test, and Heteroscedasticity Test, Test The hypothesis consists of the T-Test, F Test, Coefficient of Determination, and Multiple Linear Regression Test with the help of the Eviews 10.0 application. The results of this study indicate that partially (t-test) the firm size variable has a significant positive effect on Islamic Social Reporting. Partially, the profitability variable has a significant positive effect on Islamic Social Reporting. Partially, leverage has a significant positive effect on Islamic Social Reporting. Simultaneously (F test) the variables of firm size, profitability, and leverage have a significant effect on the disclosure of Islamic Social Reporting.